The Grim House - Molesworth, Mrs., 1839-1921; Goble, Warwick, 1862-1943 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Grim House" by Mrs. Molesworth is a novel written in the early 20th century. This story seems to revolve around themes of mystery and discovery, focusing on the lives of its main characters, particularly Regina Fitzmaurice, as she navigates her own identity and the enigma surrounding the occupants of the titular Grim House, a secluded residence linked to a family of intriguing but isolated individuals. As the characters begin to explore their relationships and the secrets entwined with this peculiar household, the narrative promises to explore deeper connections and personal growth. At the start of the novel, we are introduced to Regina and her family as they prepare to leave England for a spa in Germany due to her mother's health concerns. Soon after, they arrive at Weissbad, where Regina meets Isabel Wynyard, a young woman who piques her curiosity. During their time together, Isabel shares a peculiar history about the inhabitants of the Grim House, which lies nearby and has been long speculated about. Regina's interest in the mysterious family grows, particularly after an encounter with one of its members$1 (Ba young man who disappears as quickly as he arrives, prompting both intrigue and questions about the family's tragic past. This opening effectively sets the stage for a narrative rich in character dynamics, secrets, and the exploration of life beyond the confines of their differences. (This is an automatically generated summary.)s
Release date is 2013-10-03
Produced by Nick Hodson of London, England
Keywords: England -- Social life and customs -- 19th century -- Fiction; Young women -- Fiction; Families -- Fiction